2017
DOI: 10.1007/s40618-017-0801-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of a spray formulation containing Visnadine in women self-reporting sexual symptoms: a randomized double-blind placebo-controlled pilot study

Abstract: On demand, 1-month use of Visnadine spray displayed positive effects on sexual function in women with and without FSD and it was well tolerated. Topical Visnadine may not only be part of multimodal strategies to manage clinically relevant sexual symptoms but also simply to help women to enhance their subjective impaired perception of sexual response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The 3 Visadine interventions are applied in different ways: One of them evaluated the use of spray on demand [15], another evaluated both on demand and daily use, without placebo group [20], whilst a further study assessed the use of Visnadine oil [21]. Both spray and oil produced differences in the FSFI score with respect to placebo [15] [21], although the oil intervention was a pilot study. The other study found results to indicate the efficacy of both daily and on-demand use in women with HSDD [20].…”
Section: Resultsmentioning
confidence: 99%
“…The 3 Visadine interventions are applied in different ways: One of them evaluated the use of spray on demand [15], another evaluated both on demand and daily use, without placebo group [20], whilst a further study assessed the use of Visnadine oil [21]. Both spray and oil produced differences in the FSFI score with respect to placebo [15] [21], although the oil intervention was a pilot study. The other study found results to indicate the efficacy of both daily and on-demand use in women with HSDD [20].…”
Section: Resultsmentioning
confidence: 99%
“…It interacts with the type 1 calcium channels at the level of the smooth muscles, causing an increase in the local flow. It has been observed that the local administration of a spray based on visnadine 10 minutes before sexual intercourse has a positive effect, so it is also a candidate among the non-hormonal alternatives to be used in the treatment of GSM in BCS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Chez la femme, l'utilisation de lubrifiant et/ou d'un traitement substitutif hormonal permet de diminuer la sécheresse vaginale et les dyspareunies. 22 Enfin, la présence d'une stomie mais aussi le cancer lui-même pouvant modifier l'image de soi, et de ce fait, entraîner des difficultés dans la relation de couple, le sujet est abordé lors de la consultation par le chirurgien. Si besoin, un sexologue est impliqué dans la prise en charge du patient.…”
Section: Des Dysfonctions Sexuelles Accessibles Au Traitementunclassified